TINGKAT PENGETAHUAN REMAJA SMA TENTANG PENDIDIKAN SEKS DAN SIKAP REMAJA SMA TENTANG SEKS BEBAS - Hermina Humune (Jurnal Kebidanan Akademi Kebidanan Griya Husada Surabaya, 2018)
Nowadays free sex life has spread among teenagers because of their lack of knowledge about sex and environmental factors that greatly influence adolescent sex behavior. The 2014 survey conducted by adolescents by the BKKBN said 63% of teenagers in several major cities in Indonesia including East Java had premarital sex. Drop Out Numbers of SMA Negeri 1 Turen students were 3.69% majority because they were pregnant out of wedlock. The results of the preliminary study on March 18, 2016 out of 8 students interviewed there were 87.5% of high school students with less knowledge about sex education. The purpose of this study was to find out the High School Youth Knowledge Picture about Sex Education and the Attitude of High School Adolescents about Free Sex in Turen 1 High School. Method: This study uses descriptive methods. The population is taken from all SMA 1 Turen students in the 2016/2017 school year as many as 892 students. Samples were taken using the technique of "accidental sampling" as many as 167 high school teenagers. The data is then classified, frequency tabulation is made, cross tabulation is then concluded. Results: Of 167 adolescents found 53.89% of adolescents had good knowledge about sex education, 56.89% of adolescents had the attitude of agreeing not to have free sex, whereas from cross tabulation who had good knowledge about sex education and had the attitude of agreeing not to have free sex as many as 57.89% of adolescents. Discussion: After doing research, it can be concluded that the level of knowledge of high school adolescents about majority sex education is good. Midwives as implementers are expected to work with high school teachers to provide material on reproductive health education and parents are expected to provide sex education early in adolescents.